Molecular cloning, expression, and sequence of the pilin gene from nontypeable Haemophilus influenzae M37. - Coleman, T (1991)
Nontypeable Haemophilus influenzae M37 adheres to human buccal epithelial cells and exhibits mannose-resistant hemagglutination of human erythrocytes. An isogenic variant of this strain which was deficient in hemagglutination was isolated. A protein with an apparent molecular weight of 22,000 was present in the sodium dodecyl sulfate-polyacrylamide gel profile of sarcosyl-insoluble proteins from the hemagglutination-proficient strain but was absent from the profile of the isogenic hemagglutination-deficient variant. A monoclonal antibody which reacts with the hemagglutination-proficient isolate but not with the hemagglutination-deficient isolate has been characterized. This monoclonal antibody was employed in an affinity column for purification of the protein as well as to screen a genomic library for recombinant clones expressing the gene. Several clones which contained overlapping genomic fragments were identified by reaction with the monoclonal antibody. The gene for the 22-kDa protein was subcloned and sequenced. The gene for the type b pilin from H. influenzae type b strain MinnA was also cloned and sequenced. The DNA sequence of the strain MinnA gene was identical to that reported previously for two other type b strains. The DNA sequence of the strain M37 gene is 77% identical to that of the type b pilin gene, and the derived amino acid sequence is 68% identical to that of the type b pilin.